Peripheral White Blood Cell Subsets in Metastatic Colorectal Cancer Patients Treated with Cetuximab: The Potential Clinical Relevance - Matić, Ivana Z.; Kolundžija, Branka; Damjanović, Ana; Spasić, Jelena; Radosavljević, Davorin; Đorđić Crnogorac, Marija; Grozdanić, Nađa; Juranić, Zorica D. (Frontiers in Immunology, 2018)
It was demonstrated that cetuximab-induced tumor regression is based on the effects exerted by immune cells included mainly in the innate immune response. Therefore, the focus of this study was to explore the alterations in the percentages of CD16+, and/or CD56+ lymphocytes, which are comprised of NK cells, and minority of CD56+CD3+ cells, in patients with metastatic colorectal cancer before or 2 months after the treatment with cetuximab-based regimens associated with the response to therapy. The changes in the percentages of lymphocytes and granulocytes in these patients were evaluated as well. We enrolled 50 patients with wild-type KRAS metastatic colorectal cancer. Disease progression was observed in 11/50 patients (non-responders), while other patients achieved partial response or stable disease (responders). Control groups included up to 72 healthy individuals. A significant decrease in the percentages of CD56+ and CD16+CD56+ lymphocytes together with a significant decrease in the percentage of lymphocytes and an increase in the ratio of granulocyte to lymphocyte percentages were observed in patients with metastatic colorectal cancer before therapy, compared with those in the healthy individuals. In contrast to those in the responders, the percentage of CD16+ lymphocytes in the overall white blood cell pool was shown to be significantly decreased in the non-responders, together with a significantly decreased percentage of lymphocytes, a significantly increased percentage of granulocytes, and an increased ratio of granulocyte to lymphocyte percentages before treatment compared with those in the healthy controls. Two months after the initiation of the treatment, significantly decreased percentages of CD16+, CD56+, and CD16+CD56+ lymphocytes were observed in patients, compared with those determined in the healthy controls. The same changes in the amounts of circulating immune cells were also observed in the responder subgroup, but the percentages of CD16+, CD56+ and CD16+CD56+ lymphocytes 2 months after treatment in the non-responder group did not differ significantly in comparison with healthy individuals. Considerable alterations of immune cell percentages observed in patients with metastatic colorectal cancer with disease progression indicate that the assessment of peripheral white blood cell architecture before treatment initiation may be clinically relevant.